Emery-Dreifuss muscular dystrophy type 2 associated (?) with mild peripheral polyneuropathy - Madej-Pilarczyk, Agnieszka; Kotruchow, Katarzyna; Kabzinska, Dagmara; Cegielska, Joanna; Kochanski, Andrzej; Hausmanowa-Petrusewicz, Irena (Folia Neuropathologica, 2015)
In recent years numerous mutations in the LMNA gene encoding lamin A/C were shown to segregate with a wide spectrum of phenotypes. A recurrent p.R377H mutation in the LMNA gene was reported in patients with Emery-Dreifuss dystrophy (EDMD2) with various ethnic backgrounds. We present a patient with EDMD2 caused by a p.R377H mutation, associated with mild peripheral polyneuropathy. The analysis of peripheral myelin protein 22 (PMP22), ganglioside induced differentiation-associated protein 1 (GDAP1), gap junction β-1 protein (GJB1), and myelin protein zero (MPZ) genes did not reveal mutations; however, we identified a new sequence intronic variant in the mitofusin 2 (MFN2) gene of unknown pathogenic significance. A complex phenotype in the presented patient might depend either on single mutation in the LMNA gene or on bigenic defect; therefore, a wide genetic investigation is needed to elucidate the molecular background of EDMD2/polyneuropathy in this case.